Artificial Intelligence-based Outpainting Technology: TikTok Effect Features in the Perspective of Elegant Design Composition - Achmad Nur Kholis; Setyo Budi; Desy Nurcahyanti (School of Design Universitas Pelita Harapan, 2024)
Outpainting is one of art technologies based on artificial intelligence. Feature contained in TikTok application is able to expand uploaded the image. The image expansion system is supported by application of AI technology that is able to fill in empty parts of original image. this benefit can be achieved by identifying work patterns and understanding results of feature. It is necessary to understand concept of applying AI technology to produce images that are wider than the original photo. Therefore, an attempt was made to examine content results of Outpainting from perspective of elegant composition design. The experiment was conducted by uploading two photos that have different compositions, objects, complexity, and details of each image. In addition, the discussion of output results of technology is to find advantages and disadvantages of Outpainting feature found in TikTok application. Research strategies uses a descriptive process with trials and literature sources so as to explore good quality and in-depth data.